Analisis Kinerja Keuangan pada PT HM Sampoerna Tbk dengan Pendekatan Rasio Likuiditas dan Profitabilitas - Lubis, Jey Bremana Ramadan; Ikhsan, Arfan (Asosiasi Dosen Akuntansi Indonesia, 2025)
This research aims to analyze the financial performance of PT HM Sampoerna Tbk for the 2019–2023 period using profitability and liquidity ratios. The study evaluates the company's ability to meet its financial obligations and generate financial outcomes. The method used includes ratio analysis, such as the current ratio, quick ratio, cash ratio, net profit margin (NPM), return on equity (ROE), and return on assets (ROA) which are compared with industry standards. The research results show 172% in 2023, below the industry standard of 200%. The quick ratio and cash ratio have also decreased drastically, with a cash ratio of only 12% in 2023, far below the standard of 50%. On the profitability side, NPM, ROA, and ROE have also decreased, with NPM of 7% and ROA of 15% in 2023, both below industry standards. In conclusion, PT HM Sampoerna Tbk needs to improve its liquidity and profitability to maintain competitiveness in the industry